2017
DOI: 10.1159/000479846
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction and Altered Renal Metabolism in Dahl Salt-Sensitive Rats

Abstract: Background/Aims: The kidney plays a critical role in the control of blood pressure and its elevation in salt-induced hypertension. Mitochondrial dysfunction, especially in energy metabolism, has been associated with hypertension. Here, we aimed to investigate mitochondrial function and metabolic features in renal mitochondria of Dahl salt-sensitive (SS) rats to gain further insight into the relationship between mitochondrial metabolism and predisposition to hypertension. Methods: In this study, SS rats fed low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…Besides, high intake of salt further exacerbates the imbalance between these factors in diabetic mice, leading to aggravation of kidney damage. Previous studies also suggested that high-salt aggravated renal mitochondrial dysfunctions (Wang et al, 2017). These data highlight that we may prevent mitochondrial dysfunction by reducing dietary salt intake, thereby restoring the balance of renal tubular fatty acid metabolism and improving renal function.…”
Section: Discussionsupporting
confidence: 60%
“…Besides, high intake of salt further exacerbates the imbalance between these factors in diabetic mice, leading to aggravation of kidney damage. Previous studies also suggested that high-salt aggravated renal mitochondrial dysfunctions (Wang et al, 2017). These data highlight that we may prevent mitochondrial dysfunction by reducing dietary salt intake, thereby restoring the balance of renal tubular fatty acid metabolism and improving renal function.…”
Section: Discussionsupporting
confidence: 60%
“…similar between SS and SS.13 BN rats on a 0.4% salt diet, while mitochondrial membrane potential and ATP production rate are lower in SS rats 63 . Treatment with a 4% NaCl diet for 7 or 21 days resulted in lower ratios of ATP/ADP, GTP/GDP, and NADH/ NAD + in the glomeruli, but not the cortical tissue, of SS rats 64 .…”
Section: Role Of Renal Metabolism In Hypertensionmentioning
confidence: 72%
“…We believe that these discrepancies may be attributed to mechanistic dissimilarities in the origin and progression of hypertension in SHR and Dahl SS rats. A recent manuscript by Wang et al (2017) established that renal mitochondria from Dahl SS rats fed HS diet (8%, 2 weeks) exhibit a lower activity of fumarase, isocitrate dehydrogenase, and succinyl-CoA synthase compared with SS.13BN salt-resistant control rats, as well as reduced ATP production, membrane potential, and SOD activity. Our data indicated that similar mitochondrial impairment manifested in Dahl SS rats when a lesser salt challenge was introduced (4%, 3 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, He et al (2014) demonstrated that mitochondrial abnormalities can be observed in the mTAL of SS rats before the development of histologically detectable injury. Later, Wang et al (2017) provided evidence that renal mitochondria of Dahl SS rats displayed metabolic alterations and dysfunctions, aggravated by an increase in salt intake. Through transcriptomic analyses of renal medullary biological pathways, they established that mitochondrial TCA cycle and cell energetics are crucial for the molecular networks relevant to salt-sensitivity Evans et al, 2018).…”
Section: Introductionmentioning
confidence: 99%